Menstrual cycle effects on sacculocollic reflex pathway. (2nd October 2017) - Sinha, Sujeet Kumar; Neupane, Anuj Kumar; Gururaj, Krithika
Abstract: Introduction : Female sex hormones such as oestrogen and progesterone are found to have direct effects in the sensitivity of cochlea, till central auditory cortex by bringing the variation in vascularity in these regions. The aim of the present study was to assess the influence of sex hormones produced during menstrual cycle on the sacculocollic reflex pathway. Method: Twenty female subjects in the age range of 18–25 years with no vestibular pathologies participated in the study. Cervical vestibular evoked myogenic potential test was administered on all the subjects in three phases of menstrual cycle, that is, follicular phase (1–4 days), luteal phase (12–15 days) and menstrual phase (22–25 days). Results: Friedman Chi-square test of difference among repeated measures was done to check the significant differences in mean latency and amplitude values of cVEMP across three phases of menstrual cycle. Although there were differences in the mean latency and amplitude of cVEMP peaks across three phases of menstrual cycle, the statistical analysis revealed no significant effect of different phases of menstrual cycle on the latency or amplitude parameters of cVEMP. Conclusions: There is no significant effect of different phases of menstrual cycle on the latency or amplitude parameters of cVEMP.